Elastic behaviour of knitted fabrics for compression arm sleeves - Cruz, Juliana (2012)
In the present work, mechanical behaviour of compression arm sleeves based on knitted fabrics has been reported. Rib fabrics were developed using 95% polyamide knitting yarns and 5% polyamide covered elastane yarns as inlays using stockings technology. Samples were produced varying the characteristics (fineness of elastane core and polyamide cover) of elastane yarns in order to investigate its influence on the performance of knitted arm sleeves. The performance of developed arm sleeves was characterized in terms of level of compression that can be achieved as well as the permanent deformation and energy dissipation, which occurs during stretching. It was observed that the compression performance improved significantly with the linear density of elastane core and the improvement is higher for finer cover yarns. However, the energy dissipation and permanent deformation in the first stretching cycle also increased with the fineness of elastane core and therefore, proper selection of elastane yarn is extremely necessary to achieve required degree of compression with minimum permanent deformation while stretching.